Peran Pendidikan dalam Mengelola Keberagaman Masyarakat Multikutural di Indonesia - Rendi Rendi; Gresia Monika Sinaga; Semuel Linggi Topayung (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Maintaining the original cultural identity within a multicultural society amidst rapid globalization while remaining open to external changes and influences is a significant challenge. This tension is exacerbated by the impact of information technology, which can disseminate foreign values and ideologies, particularly affecting the youth. This study employs a descriptive qualitative method, involving research that generates descriptive data based on the community's statements that the author investigates. The research aims to describe the phenomena occurring and underscores the need for education to uphold values aligned with national identity and manage cultural diversity wisely to prevent social conflicts. Education plays a crucial role in the process of socialization and individual development, serving not only as a means of transferring knowledge but also in shaping attitudes, values, and positive behaviors within the community. Through education, individuals can become people who appreciate diversity and contribute positively to diverse communities. Multicultural education, which emphasizes the importance of respecting diversity, is key to addressing social and cultural conflicts in Indonesia's diverse society. Additionally, quality education helps individuals adapt to the challenges of globalization while preserving local cultural identity, thus supporting the balance between global openness and the preservation of local values.